A eficácia dos programas de treinamento e seus impactos sobre a renda do trabalho: o caso do CASP - Yamashita, Luiz Hiroshi (2010)
This study analyzes the performance of the Course of Professional Self-Sufficiency (CASP) on 2009, in its role of preparing differentiated professionals for the job market in terms of inclusion and raising income. Statistics analysis combined with multiple regression and Binary Dependent Variable models are developed to determine the effectiveness of this program and verify: i) participate to the program implies in an increase, though modest, in labor income; ii) against the expectations of the traditional Mincerian analysis, non-white people have higher probability to be employed; iii) independent of race, male people have a tendency to get out of an unemployment situation. These results are in according to the current changes of labor market and with the level of qualification of labor demanded in the job market of Ceará.